2007
DOI: 10.1080/07408170701592556
|View full text |Cite
|
Sign up to set email alerts
|

A model-based clustering approach to the recognition of the spatial defect patterns produced during semiconductor fabrication

Abstract: Defects on semiconductor wafers tend to cluster and the spatial defect patterns of these defect clusters contain valuable information about potential problems in the manufacturing processes. This study proposes a model-based clustering algorithm for automatic spatial defect recognition on semiconductor wafers. A mixture model is proposed to model the distributions of defects on wafer surfaces. The proposed algorithm can find the number of defect clusters and identify the pattern of each cluster automatically. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Their proposed algorithm was able to identify complicated defect patterns with fewer parameters. Yuan et al in [78], [79] investigated amorphous/linear and curvilinear WM defect patterns simultaneously, and modelled them using multivariate normal distributions and PCs, respectively, extending the traditional modelbased clustering approach by considering the mixture of two different probability densities. However, their approach is mainly based on simulated results and lacks the capability to detect closed-ring shaped patterns that have been widely observed in WM defects.…”
Section: E: Clusteringmentioning
confidence: 99%
See 2 more Smart Citations
“…Their proposed algorithm was able to identify complicated defect patterns with fewer parameters. Yuan et al in [78], [79] investigated amorphous/linear and curvilinear WM defect patterns simultaneously, and modelled them using multivariate normal distributions and PCs, respectively, extending the traditional modelbased clustering approach by considering the mixture of two different probability densities. However, their approach is mainly based on simulated results and lacks the capability to detect closed-ring shaped patterns that have been widely observed in WM defects.…”
Section: E: Clusteringmentioning
confidence: 99%
“…linear, curvilinear) via various modelbased techniques. The proposed method for classification were compared to the model-based clustering approach used in [78] and it has been found that they were able to detect more clusters for three chosen WM samples. However, in [78] they were able to detect more clusters for one of the samples.…”
Section: E: Clusteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Some statistic-based methods are also applied to wafer defect detection. Hwang and Kuob [5], Yuan and Kuo [6] and Wang et al [7] proposed different probabilistic models to describe wafer defect patterns respectively. Yuan et al [8] proposed a particle filter re-detection method via correlation filters and Tsai and Luo [9] proposed a mean shift-based method for solar wafer surface defect detection.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that spatial patterns in the distribution of defects on a die can be related to the potential causes of these defects in the manufacturing process. Given the considerable time, effort, and expense of detecting and classifying spatial defect signatures manually, there has been considerable interest over the past decade in automating the process (Chen and Liu [1], Gleason et al [2], Hansen and Thyregod [3], Jun et al [4], Karnowski et al [5], Ken et al [6], Tobin et al [7], Shankar and Zhong [8], Hwang and Kuo [9], Wang et al [10], and Yuan and Kuo [11]). …”
Section: Introductionmentioning
confidence: 99%